Days at the Torunka Café : a novel - Yagisawa, Satoshi, 1977-; Yagisawa, Satoshi, 1977- (Manilla, 2025)
"Tucked away on a narrow side street in Tokyo is the Torunka Café, a neighborhood nook where the passersby are as likely to be local cats as tourists. Its regulars include Chinatsu Yukimura, a mysterious young woman who always leaves behind a napkin folded into the shape of a ballerina; Hiroyuki Yumata, a middle-aged man who's returned to the neighborhood searching for the happy life he once gave up; and Shizuku, the café owner's teenage daughter, who is still coming to terms with her sister's death as she falls in love for the first time."-- Provided by publisher.